CHALLENGES IN TEACHING LISTENING TO YOUNG LEARNERS - Author: Raximqulova Malika Sherzod qizi Scientific advisor: Teshaboyeva Nafisa Zubaydulla qizi (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
The students have limited vocabulary to understand the listening text. Furthermore students have limited time to listening exposure. Their listening exposure is still at the level of words and sentences. Difficulties in preparing the listening material based in syllabus. Most teachers feels that time management become their major challenge in organizing classroom. They have set lesson plan, but sometimes the lesson does not work exactly the same. They have to work with mixed-level students, with students with learning difficulties, and with learners who are coming from different backgrounds. Teachers should be aware that it is part of teachers’ primary duty to cope with every student. Most students can learn a foreign language to some level, but there are many reasons why their improvements are not achieved significantly.